(untitled) (Revista Archai, 2019)
The study aims to contribute to understand the Vitruvian design system through the analysis of the temples described in the text leading to the three key concepts related: proportio, commensus and commodulatio. At first, it is proposed a conceptual discussion about the origin of the compositional elements, and further it is discussed the concept of proportio as an operation of sizing and scaling these elements individually. Analyzed the definition and types of elements, it is proposed to continue the discussion on the relationship that must be built as a way of associating elements in a consistent way, leading to the notion of symmetria, understood as an ideal state in which the elements maintain dimensional and/or geometrical relationships between them, creating a relational harmony. From the operational point of view, it is sought to demonstrate that the Vitruvian symmetria is fetched from two types of relations: a modular (commodulatio) and a dimensional (commensus).